Business Analysis Techniques 123 essential tools for success - Cadle, James; Paul, Debra; Hunsley, Jonathan; Reed, Adrian; Beckham, David; Turner, Paul (BCS, The Chartered Institute for IT, 2021)
Business analysis is about identifying business needs and formulating workable solutions to business problems. It requires the widest possible array of tools and the professional ability to use each one when and where it is needed.This new edition provides a comprehensive single source of 123 business analysis techniques, offering practical guidance on how and when to apply them within a clear BA service framework. This book complements Business Analysis, also published by BCS.